2021
DOI: 10.1186/s12884-021-03723-7
|View full text |Cite
|
Sign up to set email alerts
|

The application of late amniocentesis: a retrospective study in a tertiary fetal medicine center in China

Abstract: Background To assess the indications and complications of late amniocentesis and the advanced genetic test results in a tertiary university fetal medical medicine unit. Methods In this retrospective study, women that underwent amniocentesis at 24+ 0 to 39+ 4 weeks, between January 2014 and December 2019, were recruited. Indications, complications, genetic test results, and pregnancy outcomes were reported for each pregnancy and compared with those … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
5
7
0
Order By: Relevance
“…Our cohort of 483 fetal VUS is the second largest reported to date. Our live birth rate for fetuses with a VUS (64%) was higher than for those with a pCNV (20%) and was within the range reported in other fetal VUS cohorts (35%–90%) 10–13,15,16,19 . Similarly to Chen et al., who followed up 721 fetal VUS, we found that an inherited VUS was more likely to result in a live birth than a non‐inherited VUS 17 .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Our cohort of 483 fetal VUS is the second largest reported to date. Our live birth rate for fetuses with a VUS (64%) was higher than for those with a pCNV (20%) and was within the range reported in other fetal VUS cohorts (35%–90%) 10–13,15,16,19 . Similarly to Chen et al., who followed up 721 fetal VUS, we found that an inherited VUS was more likely to result in a live birth than a non‐inherited VUS 17 .…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of pCNVs in our cohort was 3.3%, which was similar to that reported in a published review of 23,865 pCNVs 29 . Our study of 230 pCNVs is the largest to include birth outcomes, with previous publications containing smaller cohorts (range 5–93) and/or only reporting perinatal outcomes for a small subset 10–14,18 . Our summary statistics on preterm birth and low birth weight provide general prognostic information that can be used for counseling couples about obstetric outcomes for pCNVs, particularly for rare pCNVs where data on obstetric outcomes are lacking and planning ongoing management in a high risk model of prenatal care.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations